Niat Patuh Relawan Pajak dan Memahami Ajaran Tri Nga - Kusuma Wardani, Dewi; Devi Wulandari, Andini (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine if students' intentions to comply with tax laws are influenced by their participation as tax volunteers and comprehension of nga. The descriptive, quantitative method is used in this study. Google Form-linked questionnaires were distributed for data collection. Students in Yogyakarta who had participated in the tax volunteer program and those who had not participated in the program were the samples used in this study. There were 111 respondents in total. In this study, convenience sampling, a non-probable sampling method, was used for sampling. A multiple linear regression model was used for the data analysis. The findings demonstrated that tri-nga comprehension influenced tax compliance intentions and student participation as tax volunteers had a positive effect on tax compliance intentions. Then, at that point, according to the consequences of the coefficient of assurance (R2) of 0.713 or 71.3% it tends to be reasoned that understudy supports in becoming assessment volunteers and comprehension of tri nga influences charge consistency aims by 71.3% while the excess 28.7% is affected or made sense of by different variables not involved with this model.